2013
DOI: 10.1371/journal.pone.0078692
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Child Stunting in India: A Comprehensive Analysis of Socio-Economic, Nutritional and Environmental Determinants Using Additive Quantile Regression

Abstract: BackgroundMost attempts to address undernutrition, responsible for one third of global child deaths, have fallen behind expectations. This suggests that the assumptions underlying current modelling and intervention practices should be revisited.ObjectiveWe undertook a comprehensive analysis of the determinants of child stunting in India, and explored whether the established focus on linear effects of single risks is appropriate.DesignUsing cross-sectional data for children aged 0–24 months from the Indian Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
154
7
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(215 citation statements)
references
References 87 publications
34
154
7
9
Order By: Relevance
“…A study based on data from 25 African DHSs found that non-singletons tend to be more malnourished than singletons [25]. Families with multiple births should be considered among the primary target for interventions designed to improve child nutrition [26]. Our finding that maternal education and nutritional status were correlated with a child's nutritional status is consistent with previous reports [16].…”
Section: Discussionsupporting
confidence: 91%
“…A study based on data from 25 African DHSs found that non-singletons tend to be more malnourished than singletons [25]. Families with multiple births should be considered among the primary target for interventions designed to improve child nutrition [26]. Our finding that maternal education and nutritional status were correlated with a child's nutritional status is consistent with previous reports [16].…”
Section: Discussionsupporting
confidence: 91%
“…Male children were also more likely to be stunted compared to female children. This relationship has been reported in the literature from developing countries including Ghana [14,26], Tanzania [27], Ethiopia [24], Cambodia [3] and India [28]. In spite of this widespread identification of the male susceptibility to stunting, the exact factors underlying it have yet to be well understood [14] but likely to be biological [29].…”
Section: Discussionmentioning
confidence: 86%
“…Age is a strong predictor, a finding that is consistent with the literature, where age was pointed out as a relevant factor for intervention, suggesting an interval before and after twenty four months old (Fenske et al, 2013;Bryce et al, 2008). About the positive association with female children, Grab (2009) also find that the HAZ values are significantly better for girls than for boys.…”
Section: Estimation Results For the Age Group Between Six To Twenty Fsupporting
confidence: 83%